2014
DOI: 10.1371/journal.ppat.1004467
|View full text |Cite
|
Sign up to set email alerts
|

CD4 Depletion in SIV-Infected Macaques Results in Macrophage and Microglia Infection with Rapid Turnover of Infected Cells

Abstract: In rhesus macaques (RMs), experimental depletion of CD4+ T-cells prior to SIV infection results in higher viremia and emergence of CD4-independent SIV-envelopes. In this study we used the rhesus recombinant anti-CD4 antibody CD4R1 to deplete RM CD4+ T-cells prior to SIVmac251 infection and investigate the sources of the increased viral burden and the lifespan of productively infected cells. CD4-depleted animals showed (i) set-point viral load two-logs higher than controls; (ii) macrophages constituting 80% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
109
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(131 citation statements)
references
References 40 publications
(55 reference statements)
7
109
0
2
Order By: Relevance
“…Although CD4-independent viruses have been observed in vivo, particularly in nonhuman primate models of pathogenic SIV infection, they typically appear in the setting of highly immunocompromised hosts with advanced neurological or pulmonary complications (44,58,69) at sites where nonlymphoid cells (primarily macrophages) with little or no CD4 are infected. In rhesus macaques depleted of CD4 T cells with anti-CD4 antibodies prior to SIVmac infection, CD4-independent viruses rapidly appeared, in association with SIV encephalitis and macrophage infection (46,53), indicating that this phenotype can readily emerge in vivo. Because CD4-independent viruses are characteristically neutralization sensitive, it is likely that they are strongly selected against during typical pathogenic infection (32,48,49,97).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although CD4-independent viruses have been observed in vivo, particularly in nonhuman primate models of pathogenic SIV infection, they typically appear in the setting of highly immunocompromised hosts with advanced neurological or pulmonary complications (44,58,69) at sites where nonlymphoid cells (primarily macrophages) with little or no CD4 are infected. In rhesus macaques depleted of CD4 T cells with anti-CD4 antibodies prior to SIVmac infection, CD4-independent viruses rapidly appeared, in association with SIV encephalitis and macrophage infection (46,53), indicating that this phenotype can readily emerge in vivo. Because CD4-independent viruses are characteristically neutralization sensitive, it is likely that they are strongly selected against during typical pathogenic infection (32,48,49,97).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CD4-independent viruses likely are strongly selected against in vivo (32,48,49). Nonetheless, although not strictly CD4 independent, HIVs and SIVs with the ability to utilize low levels of CD4 for entry are well described, and this phenotype has been proposed to contribute to the infection of macrophages and microglial cells, which exhibit a lower density of CD4 than T cells (32,(43)(44)(45)(50)(51)(52)(53)(54)(55)(56)(57). For one neuropathic SIV isolate, its ability to cause AIDS encephalopathy in macaques correlated with the infection of brain-derived endothelial cells that expressed CCR5 but not CD4 (58).…”
mentioning
confidence: 99%
“…It was recently suggested that myeloid cells in the gut and lymphoid tissues from SIV-infected primates are resistant to infection and acquire SIV DNA primarily through the phagocytosis of infected T cells (90). However, it was reported that macrophages in lymph nodes and mucosal tissues get heavily infected in macaques depleted in CD4 ϩ T cells (91) and that the uptake of HIV-infected T lymphocytes by blood-derived macrophages leads to their infection (92). Macrophages are functionally and phenotypically extremely heterogeneous among anatomical sites.…”
Section: Discussionmentioning
confidence: 99%
“…BAL, BaL viral Env protein; JRCSF, viral Env protein; AID, amplicon identifier; PID, patient identifier. been described during late-stage infection with a highly pathogenic X4 simian-human immunodeficiency virus (SHIV) and early in infection with simian immunodeficiency virus (SIV) when the animals were depleted of CD4 ϩ T cells using an anti-CD4 antibody (2,19). Collectively, these studies suggest that macrophage-tropic viruses evolve when CD4 ϩ T cells become limiting.…”
mentioning
confidence: 98%
“…Typically, this diversity has been analyzed as that of the viral population in the blood; however, virus can also be detected in other bodily fluids (reviewed in reference 1). Most virus detected in the blood is likely produced in lymphoid tissues that are not themselves easily sampled; thus, our knowledge of HIV-1 diversity across tissues is limited (2). Furthermore, this limitation affects our ability to analyze the possible unequal distributions of viral diversity throughout the infected host, which could affect treatment and cure efforts.…”
mentioning
confidence: 99%